2010
DOI: 10.1021/jp910759n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Shape on Freezing and Melting Temperatures of Water

Abstract: To examine the effect of pore shape on freezing and melting temperatures of water, we measured X-ray diffraction patterns from water confined in four kinds of ordered mesoporous silicas with thin carbon films on the pore wall and three kinds of the inverse carbon replicas during freezing and melting processes. The melting temperature of the pore ice revealed a good correlation with the capillary condensation pressure of nitrogen at 77 K, whereas the freezing temperature of the pore water did not. This indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 41 publications
(103 reference statements)
6
36
0
Order By: Relevance
“…The result indicated that Ag clusters were uniformly confined in the nanochannels of mesoporous TiO 2 with an obvious confinement effect, and showed excellent solar‐light‐driven photocatalytic performance. Confinement of water in ordered mesoporous silica containing thin carbon films coated on the channel wall was carried on by Morishige et al, to study the channel shape effect on melting and freezing temperatures of water by X‐ray diffraction . It was indicated the melting temperature of ice in the nanochannel was well correlated in with the nitrogen condensation pressure at 77 K, but the freezing temperature of water in the nanochannel was not.…”
Section: Wettability In 3d Nanochannelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated that Ag clusters were uniformly confined in the nanochannels of mesoporous TiO 2 with an obvious confinement effect, and showed excellent solar‐light‐driven photocatalytic performance. Confinement of water in ordered mesoporous silica containing thin carbon films coated on the channel wall was carried on by Morishige et al, to study the channel shape effect on melting and freezing temperatures of water by X‐ray diffraction . It was indicated the melting temperature of ice in the nanochannel was well correlated in with the nitrogen condensation pressure at 77 K, but the freezing temperature of water in the nanochannel was not.…”
Section: Wettability In 3d Nanochannelsmentioning
confidence: 99%
“…2D nanochannels comprised of graphene, mica, gold, reduced graphene oxide (rGO), and graphene oxide are studied to understand the confined 2D nanochannels wettability. The utilization of 3D nanochannels for wettability research contains porous carbon, porous metal, mesoporous silica, porous titanium dioxide, shale nanopores, and metal‐organic frameworks (MOFs) . The central schematic diagram of Figure shows wettability and nonwettability in 1D nanochannels, 2D nanochannels, and 3D nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…The melting occurred in a temperature range that is lower than that of bulk water, whatever the surface decoration, which is in agreement with that reported for functionalized SBA-15 or MCM-41. [43][44][45][46][47][48][49] Table 1 lists the melting temperature shifts ΔT m , with ΔT m = T m -273 K where T m is the temperature at the peak extremum. One may wonder if ΔT m is influenced by either the chemical nature of the functionalized surface or the pore diameter since it differs from one sample to another.…”
Section: Properties Of the Confined Watermentioning
confidence: 99%
“…Condensates embedded in nanometer wide vacancies of mesoporous substrates were exploited intensely to study the influence of these effects on known bulk properties of matter. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Simple van der Waals systems as rare gases in confinement were in the focus of interest as well as more elaborate quantum liquids and solids like helium or hydrogen isotopes. [9][10][11][12] Dioxygen O 2 was also among the extensively studied pore condensates.…”
Section: Introductionmentioning
confidence: 99%